Nhận diện hình ảnh và tính cách thương hiệu vùng liên kết du lịch Thành phố Hồ Chí Minh và 13 tỉnh, thành Đồng bằng sông Cửu Long - Võ Thị Ngọc, Thúy; Lê Cát, Vi; Phùng Thanh, Bình; Phạm Tấn, Nhật (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This research aims to understand better the destination image and destination personality in the regional linkage in tourism between Ho Chi Minh City and the Mekong Delta. This study was conducted through multiple methods with various techniques such as secondary research, in-depth interviews with tourism experts, group discussion, survey, field survey, and social listening. The finding revealed the common destination images of this region, such as rivers, boats/production boats linked with the image icons of Ho Chi Minh City. Also, this research pointed out the destination personality of the regional linkage, including friendly, sweet, safe but still young, vibrant, colorful, and always forward-looking. Additionally, the study discussed theoretical contributions and managerial implications to promote a new regional linkage in tourism between Ho Chi Minh City and Mekong Delta.
Keywords: Destination image; Destination personality; Regional linkage; Ho Chi Minh City; Mekong Delta